2019
DOI: 10.1080/1331677x.2019.1636697
|View full text |Cite
|
Sign up to set email alerts
|

Can onshore spot market progress influence offshore N.D.F. market development for the C.N.Y?

Abstract: This study utilises a time-varying wavelet analysis to examine the relationship between the onshore spot market and the offshore non-deliverable forward (N.D.F.) market of the Chinese Yuan (C.N.Y.). Given the presence of structural changes in the two markets, we did not find any stable causality during the sample period. However, in some sub-samples, we found that there is a strong nonlinear causal relationship running from the onshore spot market to the offshore N.D.F. market. Ties between the two markets are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…These markets then started growing in Latin American countries during the 1990s and subsequently expanded rapidly in Asia and Eastern Europe. Analysts and policymakers began recognizing the presence of NDF markets and their interrelationship with onshore market across several countries and regions, including Asian currencies (Colavecchio & Funke, 2008; Gu & McNelis, 2013; Ma & McCauley, 2013; Ma et al, 2004), the Korean Won (Park, 2001), the Chinese Renminbi (Colavecchio & Funke, 2008; Ding et al, 2014; Fung et al, 2004; McCauley & Shu, 2019; Su et al, 2019), the INR (Behera, 2011; Goyal et al, 2013; Guru, 2009; Kumar & Jain, 2018; Misra & Behera, 2006), and the Indonesian Rupiah (Cadarajat & Lubis, 2012). Various empirical studies found an impact of offshore markets on the onshore forward market (Cadarajat & Lubis, 2012; Park, 2001; Wang et al, 2007), onshore spot market (Behera, 2011, Goyal et al, 2013; Reserve Bank of India, 2013), and onshore futures market (Behera, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%
“…These markets then started growing in Latin American countries during the 1990s and subsequently expanded rapidly in Asia and Eastern Europe. Analysts and policymakers began recognizing the presence of NDF markets and their interrelationship with onshore market across several countries and regions, including Asian currencies (Colavecchio & Funke, 2008; Gu & McNelis, 2013; Ma & McCauley, 2013; Ma et al, 2004), the Korean Won (Park, 2001), the Chinese Renminbi (Colavecchio & Funke, 2008; Ding et al, 2014; Fung et al, 2004; McCauley & Shu, 2019; Su et al, 2019), the INR (Behera, 2011; Goyal et al, 2013; Guru, 2009; Kumar & Jain, 2018; Misra & Behera, 2006), and the Indonesian Rupiah (Cadarajat & Lubis, 2012). Various empirical studies found an impact of offshore markets on the onshore forward market (Cadarajat & Lubis, 2012; Park, 2001; Wang et al, 2007), onshore spot market (Behera, 2011, Goyal et al, 2013; Reserve Bank of India, 2013), and onshore futures market (Behera, 2011).…”
Section: Review Of Literaturementioning
confidence: 99%